GE_GERICHTE P/12222/2013 vom 17. Juni 2015 - GE Cour de justice (2015)
IN DUBIO PRO REO; DIFFAMATION; PLAINTE PÉNALE; PLAIGNANT; ACQUITTEMENT; INDEMNITÉ(EN GÉNÉRAL); HONORAIRES; AVOCAT | CP 173 ; CPP 429.1.a